The true cost of fashion - Spilsbury, Louise (Consumer nation : how to shop to change the world, 2014)
Describes the business behind fashion, covering the supply chain, the conditions of workers around the world, who makes money on the final product, and what environmental impacts fashion purchases have on the planet.